P109 Analysis of the clinical, gastroscopic, and pathological features of upper gastrointestinal lesions in Crohn's disease. (25th January 2019) - Li, M; Yang, Q; Huang, Z; Zhao, J; Cao, K; Tang, J; Fan, X; Chen, H; Huang, Y; Li, C; Zhi, M; Hu, P; et al.
Abstract: Background: With the increasing incidence of Crohn's disease (CD) of the upper gastrointestinal (UGI) tract, whether gastroscopy should be routinely performed in asymptomatic adult CD patients is controversial. We aimed to assess the prevalence of UGI involvement, determine the role of gastroscopy in the diagnosis, and assess whether UGI symptoms should be used as guidelines for gastroscopy. Methods: This cross-sectional study included consecutive patients diagnosed with CD at our centre between June 2017 and May 2018. gastroscopies and histological reviews were performed by designated endoscopists and pathologists. Ten specimens were obtained from six areas of the UGI tract (the oesophagus, gastric body, antrum and angulus, duodenal bulb, and descending duodenum). Both demographic and clinical data were collected. Results: Among the 169 included patients, endoscopic and histological lesions suspected to be of UGI CD were found in 74 (43.79%) and 106 (62.72%) patients, respectively. Seven (4.14%) patients had non-caseating granulomas, 15 (8.88%) patients had focally enhanced gastritis, and 36 (21.3%) patients had focal active gastritis. 137 (81.1%) patients had no UGI symptoms, among these, endoscopic and/or pathological abnormalities were observed in 108 (78.8%) patients. Twenty-four (75%) patients with UGI symptoms did not have any endoscopic or histological abnormalities. In total, the rates of non-caseating granulomas, focally enhanced gastritis, and focal active inflammation were significantly higher in the asymptomatic group ( p = 0.033). According to the endoscopic and histological features, 26 patients (15.4%) were identified having UGI CD involvement among 169 CD patients, and among these, 24 patients (17.5%) were asymptomatic, whereas 2 (6.3%) were symptomatic. We further observed that the frequency of characteristic histological lesions was significantly higher in the gastric antrum and angulus than in any other biopsy site ( p = 0.028). Focally enhanced gastritis and focal active inflammation had significantly higher frequencies than non-caseating granulomas in the stomach ( p < 0.01). There were no significant differences in the basic data between patients with or without endoscopic or pathological abnormalities ( p > 0.05). Conclusions: There was a high frequency of UGI involvement in adult CD patients, irrespective of the presence or absence of UGI symptoms. Confirmable characteristic UGI lesions of CD are also common, and routine gastroscopy and biopsy may be recommended for patients suspected of having or diagnosed with CD. Focally enhanced gastritis and focal active inflammation were observed to be more common than non-caseating granulomas which may helpful in the diagnosis of CD and are worth focussing on.